Schumpeter's Price Theory - Bloch, Harry (Routledge, 2017)
This book provides a comprehensive and critical examination of Schumpeter's price theory as well as providing suggestions for the further development of the theory. While Schumpeter's theories of economic development, entrepreneurship and the business cycle have received substantial attention in the literature, his price theory has been neglected. Yet, he proposes a price theory that is as radical as his treatment of other topics. The holistic nature of his theory also naturally means that a better understanding of his price theory will provide extra insight into other aspects of his theoretical framework. This volume is of great interest to those who study Schumpeter's work, as well as those who have an interest in history of economic thought, economic theory and philosophy and political economy.